Mineralocorticoid Receptor Antagonist Use and Hard Renal Outcomes in Real-World Patients With Chronic Kidney Disease. Issue 3 (March 2022) - Oka, Tatsufumi; Sakaguchi, Yusuke; Hattori, Koki; Asahina, Yuta; Kajimoto, Sachio; Doi, Yohei; Kaimori, Jun-Ya; Isaka, Yoshitaka
Abstract : Background: Real-world evidence about mineralocorticoid receptor antagonist (MRA) use has been limited in chronic kidney disease, particularly regarding its association with hard renal outcomes. Methods: In this retrospective cohort study, adult chronic kidney disease outpatients referred to the department of nephrology at an academic hospital between January 2005 and December 2018 were analyzed. The main inclusion criteria were estimated glomerular filtration rate ≥10 and <60 mL/min per 1.73 m 2 and follow-up ≥90 days. The exposure of interest was MRA use, defined as the administration of spironolactone, eplerenone, or potassium canrenoate. The primary outcome was renal replacement therapy initiation, defined as the initiation of chronic hemodialysis, peritoneal dialysis, or kidney transplantation. A marginal structural model using inverse probability of weighting was applied to account for potential time-varying confounders. Results: Among a total of 3195 patients, the median age and estimated glomerular filtration rate at baseline were 66 years and 38.4 mL/min per 1.73 m 2, respectively. During follow-up (median, 5.9 years), 770 patients received MRAs, 211 died, and 478 started renal replacement therapy. In an inverse probability of weighting-weighted pooled logistic regression model, MRA use was significantly associated with a 28%-lower rate of renal replacement therapy initiation (hazard ratio, 0.72 [95% CI, 0.53–0.98]). The association between MRA use and renal replacement therapy initiation was dose-dependent ( P for trend <0.01) and consistent across patient subgroups. The incidence of hyperkalemia (>5.5 mEq/L) was somewhat higher in MRA users but not significant (hazard ratio, 1.14 [95% CI, 0.88–1.48]). Conclusions: MRA users showed a better renal prognosis across various chronic kidney disease subgroups in a real-world chronic kidney disease population. Abstract : Supplemental Digital Content is available in the text.